STRATEGI PENGEMBANGAN USAHA BUDI DAYA IKAN NILA MELALUI PENDEKATAN EKONOMI LOKAL GUNA MENDUKUNG PROGRAM KUKAR IDAMAN (INOVATIF, BERDAYA SAING, DAN MANDIRI) DI KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Muslim, Khairul; Suhartini; Dwi, Agustina (PPM Sdirjianbang Akademi Militer, 2024)
The Kutai Kartanegara Regency Government has launched the KUKAR IDAMAN Dedication Program (Innovative, Competitive, and Independent Kutai Kartanegara) as part of the 2021-2026 RPJMD, aimed at infrastructure development and economic empowerment. Loa Kulu, as the largest fish-producing area in East Kalimantan, plays a vital role in the development of the fisheries sector, particularly in tilapia aquaculture, which is recognized through the Regulation of the Minister of Marine Affairs and Fisheries. Despite its significant potential, tilapia aquaculture faces challenges such as limited capacity among fish farmers, weak regulatory enforcement, and high production costs. This study aims to identify appropriate strategies for developing tilapia aquaculture using qualitative methods, including observation, interviews, and documentation. Analysis is conducted using the SWOT approach and local economic concepts to support the implementation of the KUKAR IDAMAN program, with the hope of enhancing the effectiveness and sustainability of aquaculture efforts in the region.